The Influence of Parenting Patterns on Stunting Incidences in Toddlers (Study in the Work Area of Sumberjambe Health Center, Kasiyan Health Center and Sumberbaru Health Center Jember Regency) - Laili, Ayik Nikmatul; Munawir, Al; Ningtyias, Farida Wahyu (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2021)
Stunting is a form of long-term reflection of the quality and quantity of food consumed is inadequate and often suffers from infectious diseases in childhood. The problem of stunting is a nutritional problem that needs attention because it can affect the quality of human resources. Stunting problems, especially those that occur in toddlers, are considered serious because stunting conditions in toddlers can cause delays in motor development and decrease intelligence levels. The type of research used in this study is an analytical observational study with a case control research design. The results of data analysis showed that there was an effect of parenting on the incidence of stunting in toddlers. The amount of risk is 5, 1 which means that families who apply good parenting to toddlers will reduce the risk of stunting. This study is in line with research conducted by Rahmayana, et al (2014) which states that there is a significant relationship between parenting patterns and the incidence of stunting. Parenting patterns of parents to children in this case is the practice of giving food is an important foundation in growth. The role of parents, especially mothers when breastfeeding their children, when giving food, how to give food to children and controlling the portion size and nutritional content in children's food will improve nutritional status so that it will reduce the incidence of stunting in children. The solution to this problem is to screen children under five to detect stunting.